PENGARUH PIJAT OKSITOSIN TERHADAP KALA I FASE AKTIF PADA IBU BERSALIN DI PMB “Y” DI KARAWANG TAHUN 2023 - Rina Dwi Anggraeni; Euis Atikah (Bajang Institute, 2024)
Labor is the birth of a baby, placenta, and amniotic membranes from the uterus to the outside world. The cause of complications in childbirth that causes increased mortality and morbidity in the mother and fetus is prolonged labor. The high number of old events during the active phase I in West Java. This research aims to know the direct and indirect influence as well as the Oxytocin massage exercise towards the first stage of the active phase in PMB “Y” In Karawang year 2023. With the method of quantitative approaches that use design cross-sectional. The population in this study were all labour women in PMB “Y” in karawang. The sample in this study were 15 respondents with purposive sampling technique. This research instrument uses partographs and observation sheets to assess the length of the first stage of the active phase. The method of analysis by SEM analysis using Smart-PLS 4. the results of the hypothesis testing above, it is known that H1 is accepted, namely there is a significant effect of Oxytocin Massage on the active phase of Phase I with a path coefficient of 0.611 and P-Value of 0.000 <0.05. Each Oxytocin Massage intervention will affect the active phase of Phase In the 95% confidence interval, the influence of Oxytocin Massage on the active phase of Phase I lies between 19.3% and 90.8%. Oxytocin Massage in influencing the active phase of Phase I has a high influence at the structural level (F Square = 0.595). The need to convey information about Oxytocin Massage is one of the efforts to deal with problems that often occur in the active phase of Phase I. Performing Oxytocin Massage is considered very important where when the mother performs a series of Oxytocin Massage properly, the influence on the active phase of Phase I will increase to 90.8%.